Magnetic Stimulation Therapy in Patients with COPD: A Systematic Review. (4th March 2018) - Polastri, Massimiliano; Comellini, Vittoria; Pacilli, Angela Maria Grazia; Nava, Stefano
ABSTRACT: Magnetotherapy (MT) is a therapeutic treatment based on the use of magnetic fields (MF) that can have an anti-inflammatory and analgesic effect. MT represents a possible treatment or an ancillary therapeutic intervention for a wide range of diseases and it is often used in the field of physiotherapeutic practices. A crucial point in the treatment of chronic obstructive pulmonary disease (COPD) patients, to counteract muscular depletion and respiratory symptoms, is represented by physiotherapy. Nevertheless, the knowledge about the application of MF as a therapeutic option in COPD patients is very limited. The purpose of the present study was to define what is currently known about the use of MF in patients with COPD. A systematic review of the literature was conducted during the month of October 2017, searching three main databases. Only those citations providing detailed informations about the use of MF to treat COPD symptoms either during an acute or a chronic phase of the disease, were selected. Following the selection process three articles were included in the final analysis. The present review focused on a total of thirty-six patients with COPD, and on the effects of the application of MF. In the majority of cases, the treatment sessions with MF were carried-out in an outpatient setting, and they differed with regard to the duration; frequency of application; dosage; intensity of the applied MF. Basing on the available informations, it seems that MF is a feasible, well tolerated, safe therapeutic option, for the treatment of motor-related COPD symptoms.